Stigma Childfree di Indonesia: Studi atas Pandangan Filsafat Kebebasan Isaiah Berlin - Elsa Azkia Yulianti (UIN Sunan Gunung Djati Bandung, 2023)
This research aims to discuss the stigma of childfree in Indonesia in the view of Isaiah Berlin's philosophy of freedom. This research uses qualitative methods with more focus on the application of descriptive-analytical methods for deepening. The analytical knife used in this research is the view of Isaiah Berlin's philosophy of freedom, while the object studied is the stigma of childfree in Indonesia. The scope of research is childfree stigma. The rest, the context of this research is childfree in Indonesia. The results of the discussion of this research show that Berlin divides the concept of freedom into two ideas. Among them are positive liberty and negative liberty. For Berlin, positive liberty is positioned as a goal in pursuing an instrumental value of the freedom project. Meanwhile, negative liberty is positioned as an instrument to make freedom a goal. This research concludes that the concept of Berlin's two ideas results in the childfree decision as a positive freedom, which is based on the master of himself as a way of life. While the negative stigma of the emergence of childfree from society as a negative freedom is a form of restraint from outsiders. This research is recommended for the community to be able to respect the decision of the chidfree perpetrator as a right in determining the way of life, by not attaching a negative stigma to the chosen childfree decision.